Reforma al sistema procesal oral laboral para garantizar el cumplimiento de los principios de eficacia, celeridad y economía procesal, previo a garantizar los derechos del trabajador - Jaramillo Gaona, Alicia Nathaly (2016)
The present titled investigative work of thesis of Degree: it "reforms to the oral labor procedural system to guarantee the execution of the principles of effectiveness, velocity and procedural economy, previous to guarantee the worker's" rights, it arose of the deep analysis carried out to the labor national legislation, in the concerning thing to the application of the principles of Effectiveness, Velocity and Procedural Economy to the moment to apply them in the oral labor trial that you/they should be executed from a beginning of the previous process, like it is made in the executive trial, previous to guarantee the worker's rights, so that the worker achieves this way to charge his owing remunerations. The theoretical, juridical and doctrinal storing, the study of concrete cases, the application of surveys and interviews, he/she allowed to obtain approaches with clear and precise basics, of very grateful bibliography that you/they contributed to the verification of the objectives and the contrastación from the outlined relating hypotheses to this practice; as much the Constitution as the other laws labor tipifican the rights of the workers, but they are the employers that don't make effective the right to the remuneration that you/they have all the workers.